PEMANFAATAN GELOMBANG MIKRO DALAM EKSTRAKSI ANTOSIANIN DARI KULIT BUAH NAGA SEBAGAI PENGGANTI RHODAMIN B UNTUK SEDIAAN PEWARNA BIBIR ALAMI - Arief Adhiksana; Andi Jumardi; Kusyanto; Rina Andriani (Journal of Research and Technology, 2017)
Today, microwave can be used in various chemical processes. The advantage of microwaves is able to deliver energy directly to the material. One of microwave application is the extraction process of natural materials. Microwaves can be used to reduce extraction process time of the anthocyanin from the dragon fruit skin. This research aims to determine the solvent extracted effect to the anthocyanin extraction of dragon fruit skin using microwaves. The solvent used was 95% ethanol, 85% ethanol, 75% ethanol, 95% ethanol –citric acid, 85% ethanol -acids and 75% - citric acid ethanol to the anthocyanin extraction results of dragon fruit skin extracted using microwaves. The consumption of microwave power is 400 watt with 50 gram of dragon fruits skin. Then, anthocyanin extracts are mixed with supporting materials to be made as lipstick and proposed for topical and favorite test. The best yield can be obtained by using ethanol-citric acid solvent at 25,031%.